Preparing SOP for Microbiology Laboratory: A Short Guideline - Jilani, Md. Shariful Alam; Chowdhury, Md. Moniruzzaman; Murshed, Md.; Hasan, Zahidul (Bangladesh Journal of Medical Microbiology, 2016)
No Abstract Bangladesh J Med Microbiol 2007;01(01):25-32